A COMPARISON BETWEEN PEER AND TEACHER FEEDBACK ON LEARNERS' LANGUAGEACCURAC A CASE STUDY - Wiwik Andreani (Soegijapranata Catholic University, 2009)
This study examines how peer and teacher feedback help learners improve their grammatical accuracy in their written work. It is a longitudinal case study with twelve participants of an EFL Grammar class. They did two self editing tasks and three self-correction tasks on the same written work. In doing the self-correction activities, the learners received three kinds of feedback: direct peer feedback and two kinds of indirect feedback from the teacher. The study found that indirect teacher feedback, in the form of metalanguage comments and underlining errors, gave the biggest contribution to the learners' language accuracy. However, in regard to the consistently corrected errors, peer feedback outperformed teacher feedback in its contribution. The result showed that both direct and indirect feedbacks were beneficial for the learners to raise their awareness towards becoming independent self-editors.